Impact of Emotional Intelligence in Banking Sector - Shivani Tiwari (HM Journals, 2025)
The purpose of this research is to conduct a structured analysis of the influence of emotional intelligence in Banking Sector. The sources supporting the study of emotional intelligence will be reviewed in this paper. The current study seeks to understand the concept of emotional intelligence. Recently, emotional intelligence has become a debated and crucial subject due to its importance and links to various other areas of life, leading to in-depth research. Emotional intelligence acts as the guide for emotions, thoughts, knowledge acquisition, analytical thinking, and innovative thinking. The Banking sector relies heavily on emotion. Employees in the banking industry build and sustain relationships in emotionally charged work situations where providing services is heavily reliant on emotion. Emotions have an intrapersonal impact on bank workers as well as an impact on professional relationships and service performance.